Low-temperature corrosion in large-scale biomass boilers - Farzad Jafarihonar; Emil Vainio; Leena Hupa; Mikko Hupa (npj Materials Degradation)
Abstract The shift toward biomass fuels for heat and power generation has introduced a range of new challenges for power plant technology, in particular large-scale boilers. One major challenge is the corrosion of preheaters and flue gas cleaning equipment, commonly known as low-temperature corrosion. Observations over recent decades show that this form of corrosion aligns more closely with chlorine chemistry than with sulfur chemistry. This review provides an up-to-date survey of the existing literature, with a particular focus on hygroscopic chloride salts that deliquesce and cause corrosion on cold-end surfaces.